Assessment of biocompatibility of ureasil-polyether hybrid membranes for future use in implantodontology - Oshiro Junior, João Augusto [UNESP]; Mortari, Gabriel Riquieri [UNESP]; de Freitas, Rubens Moreno [UNESP]; Marcantonio-Junior, Elcio [UNESP]; Lopes, Leandro [UNESP]; Spolidorio, Luis Carlos [UNESP]; Marcantonio, Rosemary Adriana [UNESP]; Chiavacci, Leila Aparecida [UNESP] (Taylor & Francis, 2016)
The biocompatibility of ureasil-polyether hybrid materials has been tested for future application as membrane barrier. The authors evaluated ureasil-polyether hybrids membranes with different swollen behaviors: more swellable ureasil-poliethylene oxide (ureasil-PEO) of molecular wheigth 1900g.mol−1 and less swellable ureasil-polypropilene oxide (ureasil-PPO) of molecular wheigth 400g.mol−1. The swollen behavior was monitored by SAXS measurements and in vivo assays using Rattus Norvegicus were used to study their biocompatibility. The results obtained were compared with the same treatment made with collagen commercial membranes. It was observed that for commercial collagen membranes, inflammatory levels declined after seven days. The ureasil-PEO induced a greater influx of inflammatory cells during 30 days which could be associated with the higher degree of swelling. The ureasil-PPO membranes exhibited a smaller level of inflammatory cells and are good candidates for application as biomaterial, considering their low cost, ability to deliver active molecules, and biocompatibility.
Keywords: Biocompatibility; Membranes; Ureasil-polyether hybrid materials